Prices of Factors and Good in General Equilibrium - Samuelson, Paul A. (Review of Economic Studies, 1953)
Journal Article Prices of Factors and Goods in General Equilibrium Get access Paul A. Samuelson Paul A. Samuelson Cambridge, Mass. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 21, Issue 1, 1953, Pages 1–20, https://doi.org/10.2307/2296256 Published: 01 January 1953